Digital holographic microscopy for MEMS/MOEMS device inspection and complete characterization - Singh, Vijay Raj (2015)
Digital holography became feasible since the availability of charged coupled devices (CCDs) with smaller pixel sizes, higher pixel numbers and high speed computers. Fresnel or Fourier holograms are recorded directly by the CCD and stored digitally in the computer. The reconstruction of the wavefield, which is done optically by illumination of a hologram in conventional holography, is performed by numerical methods in digital holography. In the numerical reconstruction process, not only the intensity but also the phase distribution of the stored wavefield can be computed from the digital hologram. This offers new possibilities for a variety of applications. This review article describes the principle of digital holographic microscopy (DHM) and its major applications in microelectro-optomechanical systems (MEMS/MEOMS) inspection and characterization. MEMS structures are generally realized using different material layers involving various process steps. Static and dynamic characterization of MEMS devices form an important part in carrying out their functional testing and reliability analyses. Development of a digital holography (DH) based system for micro-device inspection and characterization is presented in this review. A reflection mode hand-held type compact DH microscope system is developed based on the lensless magnification configuration. Application of the developed system is demonstrated for MEMS structures such as cantilever, diaphragms, accelerometer, microheater inspection. Further, both static and dynamic characterizations of these MEMS structures are illustrated.